Boosting linseed (Linum usitatissimum L.) production through application of micronutrients in North Western Himalaya: Boosting linseed (Linum usitatissimum L.) production through application of micronutrients in North Western Himalaya - GURUDEV SINGH; PANKAJ CHOPRA; SANDEEP MANUJA; R P SHARMA (Journal of Oilseeds Research, 2023)
In acidic soils, for getting significantly higher yield of linseed with highest monitory returns, soil application of Zn SO4 @ 25 kg / ha+ foliar application of Zn SO4 @ 0.5 % at 45 DAS should be done. However, the other best options in this regard were soil application of zinc @ 25 kg Zn SO4/ ha + Borax @ 1.5 kg/ha and soil application of Zn SO4 @ 25 kg / ha followed by foliar application of Zn SO4 @ 0.5 % + Borax @ 0.3 % at 45 DAS.